HUBUNGAN ANTARA KOMPETENSI DAN KEDISIPLINAN GURU PAK DENGAN MOTIVASI BELAJAR SISWA - Ardianus Hulu (Jurnal Teologi Biblika, 2020)
This research was intended to find out the relationship between the competence and discipline of PAK teachers and students' motivation. This research uses descriptive quantitative method, namely analysis test and validity test. This research was conducted at SMK Negeri 1 Alasa Nias Utara. the author's own area of ​​origin, in order to improve the quality of Christian religious education, especially in this school. The results of the study show that teacher competence and teacher discipline will foster motivation from students. With positive motivation possessed by students, it will facilitate achievement in education.